Critically Questioning the Discourse of Transformative Learning Theory. (February 2013) - Kucukaydin, Ilhan; Cranton, Patricia
In this article, the authors critically examine the way discourse enters into and becomes embedded in transformative learning theory, especially from the extrarational or depth psychology perspective. The authors begin by providing an overview of how transformative learning theory has developed in diverse directions, including the extrarational approach. In this latter perspective, concepts from depth psychology tend to be used to describe transformative learning, without there being a critical analysis or a common understanding of the meaning of these concepts. By treating knowledge about transformative learning as practical knowledge (from the perspective of Habermas's framework), the authors are able to critically question the knowledge claims inherent in the discourse within the extrarational approach to transformative learning theory development.